O13.5. GLUTAMATERGIC METABOLITES ASSOCIATED WITH ALTERED HIPPOCAMPAL AND STRIATAL ACTIVATION DURING NOVELTY SALIENCE IN PEOPLE WITH A CLINICAL HIGH RISK FOR PSYCHOSIS. (9th April 2019) - Allen, Paul; Modinos, Gemma; Bossong, Matthijs; Antoniades, Mathilde; Samson, Carly; Azis, Matilda; Howes, Oliver; Stone, James; Grace, Anthony; McGuire, Philip
Abstract: Background: Using Magnetic Resonance Spectroscopy (MRS) we have recently shown that, in individuals with a Clinical High Risk (CHR), transition to psychosis is associated with increased left hippocampal glutamate levels at presentation. We have also shown that relative to healthy controls (HC), CHR participants show reduced hippocampal activity during a novelty salience task when processing pure stimulus novelty. However, the extent to which elevated glutamatergic metabolite levels in CHR cohorts are related to reduced hippocampal function has yet to be investigated. Methods: Seventy-five individuals with a CHR for psychosis and 31 HC completed MRS and functional Magnetic Resonance Imaging during a novelty salience task to measure hippocampal glutamatergic metabolite levels and task-related activity (during pure stimulus novelty) respectively. In the CHR group 13 participants made a transition to psychosis at clinical follow-up (mean = 18.5 months). Three-way interactions were modeled between task-related activity, hippocampal glutamatergic metabolite levels and group (HC vs. CHR) using a Region of Interest (ROI) approach in bilateral hippocampus and striatum (which receives glutamatergic outputs from the hippocampus and is also activated during a novelty salience task). Results: The CHR group were significantly younger and had received fewer years of education than HC. CHR and HC groups were matched for gender, estimated IQ scores, tobacco and alcohol use. Ten CHR participants were receiving low doses of antipsychotic medication. There was no interaction between left hippocampal glutamate levels, task-related activity and group in either ROI. There was a significant interaction between Glx levels (combined glutamate and glutamine peaks), task related activity and group in the right hippocampus (x = 28, y = -30, z = -6; Z =3.62; p FWE = .02) and the right dorsal striatum (x = 6, y = 16, z =6; Z = 3.67 p FWE = .01). In both hippocampal and striatal ROIs the 3-way interaction was driven by a positive association between hippocampal Glx levels and activity during pure stimulus novelty in the HC group. In the CHR group however, the relationship between Glx and task-related activity was negative and largely driven by CHR participants that had transitioned to psychosis at follow-up. Discussion: Hippocampal glutamatergic metabolite levels are associated with altered functional activation in the hippocampus and dorsal striatum during a novelty salience task. These findings are consistent with previous clinical and pre-clinical work that posit a role for glutamate in hippocampal dysfunction and associated risk for psychosis.